EVALUASI DAN PENINGKATAN KOMPETENSI KADER POSYANDU DENGAN METODE LIMA LANGKAH POSYANDU - Fuady, Ikhsan; Prasanti, Ditha (JP2N : Jurnal Pengembangan Dan Pengabdian Nusantara, 2023)
Posyandu is the government's effort to improve health services for mothers and toddlers. Posyandu cadres are central figures who spearhead health services for mothers and toddlers. The low competence of posyandu cadres is a problem in itself for most rural communities. This community service (PPM) aims to evaluate and improve the competence of posyandu cadres. The service method carried out in this research was to use a five-level posyandu competition approach which was participated by 11 groups of posyandu cadres. This community service is carried out in Malangbong District, Garut Regency. The PPM participants are posyandu cadres from 11 villages in Malangbong sub-district. The posyandu cadre of each village posyandu consists of 5 cadres who will place 1 service post each. The PPM results show that cadres' initial knowledge about excellent service at Iposyandu is still relatively low. This five-step posyandu competition method is quite good in increasing the knowledge and skills of cadres in providing excellent service for mothers and toddlers in Malangbong sub-district. This recommendation from PPM suggests the need for further assistance to increase the competency of posyandu cadres in Malangbong District.